Development of Tourism in Selected European Union Countries - Natalia ZNAMIEROWSKA (Communications of International Proceedings, 2024)
The aim of the article was to investigate the development of tourism in selected European Union (EU) countries. The development of tourism is due to a change in attitudes to leisure activities and the increased mobility of society, which contributes to more frequent tourist trips. In the European Union countries, the introduction of the Schengen area, which allows for easier international travel, has also proved particularly significant. The analysis carried out has shown that tourism in the countries studied is growing, despite the difficulties the sector has experienced as a result of the COVID-19 pandemic. The analysis can serve as a prelude to further in-depth research into the development of tourism in the context of its importance to the economy in selected European Union countries. At the same time, it provides a topic for discussion on the future development of the tourism market in an era of ubiquitous global competition.
Keywords: Tourism and hospitality management; competitiveness of tourist destination; positive and negative effects of tourism; market analysis.